PENGEMBANGAN BEAUTYLEARN PADA BISNIS BIDANG USAHA KECANTIKAN - Novia Restu Windayani; Nia Kusstianti; Biyan Yesi Wilujeng; Dewi Lutfiati (Journal of Beauty and Cosmetology (JBC), 2024)
This study aims to evaluate the influence of the use of the BeautyLearn platform in improving technical and managerial skills in beauty businesses. The research method used is a survey with data collection through questionnaires distributed to entrepreneurs and workers in the beauty sector. The results showed that BeautyLearn had a significant positive impact, with 80% of respondents reporting an improvement in technical skills in the areas of makeup, skincare, and haircuts, and 75% experiencing an improvement in managerial skills, such as digital marketing and financial management. In addition, 85% of respondents appreciated the platform's flexibility in providing learning materials that can be accessed anytime and anywhere. However, around 50% of respondents experienced technical problems, such as unstable internet connections and difficulties in understanding some technical materials. Based on these findings, it can be concluded that